SAT0455 A QUALITY IMPROVEMENT INTERVENTION TO INCREASE INFLUENZA AND PNEUMOCOCCAL VACCINATION RATES IN IMMUNOSUPPRESSED INFLAMMATORY ARTHRITIS PATIENTS. (June 2019) - Murray, Kieran; Young, Francis; Low, Candice; O'rourke, Anna; Callanan, Ian; Feeney, Eoin; Veale, Douglas
Abstract : Background: Disease-related immune dysfunction and medications cause immunosuppression in inflammatory arthritis (IA)(1). EULAR and Centers for Disease Control (CDC) recommend influenza and 23-valent pneumococcal polysaccharide (PPSV23) vaccination. Previous studies show suboptimal coverage. Objectives: To increase influenza (annual) and PPSV23 (5 yearly) vaccination in immunosuppressed IA patients through a multifaceted quality improvement intervention. Methods: Between April and September 2017, IA patients completed an anonymous paper 23 question worksheet recording demographics, medical history, medications, vaccination knowledge, status and barriers. All patients on oral steroids, bDMARDs or immunosuppressant cDMARDs were included. Simultaneously, we introduced staff education sessions, point-of-care paper "Arthritis and Infection Worksheets" and "Vaccination Advice Letters". In 2018, the clinic was re-assessed. Results: 163 patients met inclusion criteria in 2017 and 262 in 2018. Patients were typical of an IA clinic (74% women, 45.4%≥60 years old, 72.7% had RA, 61.1% on cDMARDs, 53.6% on methotrexate, 46.6% on bDMARDs, 23.1% on cDMARD plus bDMARD). In 2017, 104 (65.4%) knew of the increased infectious risk of IA. In 2018, 168 (65.6%) were aware. Awareness of infection risk with medications increased from 111 (69.8%) to 172 (66.9%). Table 1 shows vaccination rates. PPSV23 rates increased from 41.0% to 47.2% (P value=0.29. Pearson Chi squared), and influenza from 61.8% to 62.1% (P value=0.95, Pearson Chi squared). Vaccination awareness was higher for influenza (Table 2 ). Most patients were informed of requirements and vaccinated by general practitioners (GPs), with <5% of patients vaccinated in hospital. In 2017, the most common reason for non-vaccination was lack of awareness. This decreased post intervention. 70% of patients had smart phone access. 78% were willing to use this for vaccination reminders. Conclusion: This study shows suboptimal vaccination awareness and uptake. Our interventions increased PPSV23 and influenza vaccination rates. There is debate about who is responsible for vaccinations. Guidelines advocate specialists sharing responsibility with GPs. 57% of rheumatologists considered GPs responsible (2). Perhaps, we should take a more active approach. References: [1] Doran MF, Crowson CS, Pond GR, O'Fallon WM, Gabriel SE. Frequency of infection in patients with rheumatoid arthritis compared with controls: a population-based study. Arthritis & Rheumatism.2002;46(9):2287-93 [2] McCarthy EM, Azeez MA, Fitzpatrick FM, Donnelly S. Knowledge, attitudes, and clinical practice of rheumatologists in vaccination of the at-risk rheumatology patient population. JCR: Journal of Clinical Rheumatology. 2012;18(5):237-41 Disclosure of Interests: Kieran Murray Grant/research support from: Newman Research Fellowship (Abbvie), Francis Young: None declared, Candice Low: None declared, Anna O'Rourke: None declared, Ian Callanan: None declared, Eoin Feeney: None declared, Douglas Veale: None declared